Emerging Policy Issues Localisation Barriers to Trade - Stone, Susan (OECD Trade Policy Papers, 2015)
Despite the predominately negative evidence of the impact of local content requirements on trade, they continue to play a significant role in trade policy. This has been particularly true since the financial crisis of 2008. The work presented here provides new evidence of the detrimental effects these policies have on the imposing country's own economy. Most empirical studies have focused on the long run inefficiencies associated with LCRs, notably in the effected sector. This paper highlights the costs to other sectors in the economy, the different impacts on intermediate versus final demand, and the declines in trade in third-party economies, despite not engaging in direct trade with the imposing country. Economies imposing LCRs experience a decrease in exports in non-LCR effected sectors and a growing concentration of domestic activity in a few targeted sectors, undermining potential growth and innovation on a broader scale. The paper concludes by offering policy alternatives